Volume 7: Operations, Applications, and Components 2006
DOI: 10.1115/pvp2006-icpvt-11-93423
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Behavior of Alloy 22 in High Nitrate Brines at Temperatures Higher Than 100°C

Abstract: Alloy 22 (N06022) may be susceptible to crevice corrosion in chloride solutions. Nitrate acts as an inhibitor to crevice corrosion. Several papers have been published regarding the effect of nitrate on the corrosion resistance of Alloy 22 at temperatures 100°C and lower. However, very little is known about the behavior of this alloy in highly concentrated brines at temperatures above 100°C. In the current work, electrochemical tests have been carried out to explore the anodic behavior of Alloy 22 in high chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Felker et al (2006) did not test lower NO 3 :Cl ratios to determine critical values needed to inhibit localized corrosion in part because lower nitrate to chloride brines are not stable at the atmospheric testing conditions of their experiments. Note that defining temperature dependent NO 3 :Cl ratios necessary to inhibit the initiation of localized corrosion should be used with caution, because systematic studies of nitrate inhibition in the Ca-Cl-NO 3 system from 100 to 150˚C indicate that nitrate inhibition is dependent on the nitrate and chloride concentrations as well as the NO 3 :Cl ratio (Ilevbare et al, 2006) in agreement with the Yucca Mountain model at temperatures less than 120˚C (Section 5.2.1).…”
Section: Role Of Nitrate On Alloy 22 Localized Corrosion At High Tempmentioning
confidence: 78%
See 3 more Smart Citations
“…Felker et al (2006) did not test lower NO 3 :Cl ratios to determine critical values needed to inhibit localized corrosion in part because lower nitrate to chloride brines are not stable at the atmospheric testing conditions of their experiments. Note that defining temperature dependent NO 3 :Cl ratios necessary to inhibit the initiation of localized corrosion should be used with caution, because systematic studies of nitrate inhibition in the Ca-Cl-NO 3 system from 100 to 150˚C indicate that nitrate inhibition is dependent on the nitrate and chloride concentrations as well as the NO 3 :Cl ratio (Ilevbare et al, 2006) in agreement with the Yucca Mountain model at temperatures less than 120˚C (Section 5.2.1).…”
Section: Role Of Nitrate On Alloy 22 Localized Corrosion At High Tempmentioning
confidence: 78%
“…Additional electrochemical studies in Ca-Cl-NO 3 brines to 160˚C and K-Na-Cl-NO 3 brines to 150˚C also report that nitrate inhibits localized corrosion of Alloy 22 (Ilevbare et al, 2006;Felker et al, 2006). Localized corrosion observed in the passive 9-month experiments suggests that NO 3 :Cl ratios above 7.4 may be required to inhibit localized corrosion at 160 and 220˚C.…”
Section: Role Of Nitrate On Alloy 22 Localized Corrosion At High Tempmentioning
confidence: 94%
See 2 more Smart Citations
“…One study contained the behavior of Alloy 22 at temperatures up to 160°C in highly concentrated calcium based chloride and nitrate brines. 24 It was reported that the inhibiting effect of nitrate for crevice corrosion is also valid up to temperatures of 160°C. 24 Corrosion at the repository site may occur only in the presence of water.…”
Section: Introductionmentioning
confidence: 99%